2009
DOI: 10.1248/jhs.55.739
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Oxidized Peroxiredoxin-3 in Cadmium- and Ceramide-induced Apoptosis of Human Neuroblastoma Cells

Abstract: Cadmium (Cd) is an environmental pollutant that produces numerous toxic effects in humans. Previous reports have demonstrated that Cd induces neurodegeneration and other diseases. To study the mechanism of Cd-induced neurodegeneration, SH-SY5Y cells were exposed to Cd. Cd-induced ceramide production was observed in the cells in a time-and dose-dependent manner. Ceramide is a well known lipid second messenger. Previous reports have shown that accumulation of ceramide, triggered by oxidative stress or anticancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Sheader et al (2006) confirm this hypothesis as they detected a strong upregulation of Prx after Cd exposure in Platichthys flesus. The oxidized form of Prx-3, on the other hand, seems to be involved in Cd-induced apoptosis in human neuroblastoma cells (Oh et al 2009). Thioredoxin (Trx) and glutaredoxin (Grx) are important compounds in the maintenance of the intracellular redox homeostasis and are kept in their reduced state via NADPH dependent thioredoxin reductases (TrxR) or GSH respectively (Meyer et al 2008).…”
Section: Thiols: a Role In The Cd-induced Antioxidative Defensementioning
confidence: 99%
See 1 more Smart Citation
“…Sheader et al (2006) confirm this hypothesis as they detected a strong upregulation of Prx after Cd exposure in Platichthys flesus. The oxidized form of Prx-3, on the other hand, seems to be involved in Cd-induced apoptosis in human neuroblastoma cells (Oh et al 2009). Thioredoxin (Trx) and glutaredoxin (Grx) are important compounds in the maintenance of the intracellular redox homeostasis and are kept in their reduced state via NADPH dependent thioredoxin reductases (TrxR) or GSH respectively (Meyer et al 2008).…”
Section: Thiols: a Role In The Cd-induced Antioxidative Defensementioning
confidence: 99%
“…Thioredoxin (Trx) and glutaredoxin (Grx) are important compounds in the maintenance of the intracellular redox homeostasis and are kept in their reduced state via NADPH dependent thioredoxin reductases (TrxR) or GSH respectively (Meyer et al 2008). Most studies indicate an enhanced oxidation of Trx1 and Trx2 redox states after Cd exposure (Hansen et al 2006;Oh et al 2009), resulting in apoptosis. This is probably due to an increased binding of Cd although a reduction in TrxR activity was also detected during Cd stress (Hodkova et al 2008).…”
Section: Thiols: a Role In The Cd-induced Antioxidative Defensementioning
confidence: 99%
“…Scholars found that PrxIII appeared an enhanced expression in some cancers (such as prostate, endometrial, colorectal, etc. ), 19–22 and some environmental chemical pollutants (such as cadmium) also increased PrxIII expression 23 . Therefore, the enhanced expression of PrxIII is considered to be related to the occurrence of tumor 24 …”
Section: Introductionmentioning
confidence: 99%
“…), [19][20][21][22] and some environmental chemical pollutants (such as cadmium) also increased PrxIII expression. 23 Therefore, the enhanced expression of PrxIII is considered to be related to the occurrence of tumor. 24 Our previous research in vivo observed that FA caused oxidative damage of bone marrow cells of mice accompanied by high expression of PrxIII, at the same time the activities and expressional levels of caspase-3 and -9 were also observed increased, indicating that mitochondrial apoptosis pathway was occurred after FA exposure.…”
mentioning
confidence: 99%